2017
DOI: 10.3201/eid2308.161861
|View full text |Cite
|
Sign up to set email alerts
|

Acute Febrile Illness and Complications Due to Murine Typhus, Texas, USA1,2

Abstract: Murine typhus occurs relatively commonly in southern Texas, as well as in California. We reviewed records of 90 adults and children in whom murine typhus was diagnosed during a 3-year period in 2 hospitals in southern Texas, USA. Most patients lacked notable comorbidities; all were immunocompetent. Initial signs and symptoms included fever (99%), malaise (82%), headache (77%), fatigue (70%), myalgias (68%), and rash (39%). Complications, often severe, in 28% of patients included bronchiolitis, pneumonia, menin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…were negative [18]. In this clinical case, the neurological and gastrointestinal symptoms rapidly resolved once the patient was started on azithromycin for Campylobacter gastroenteritis.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…were negative [18]. In this clinical case, the neurological and gastrointestinal symptoms rapidly resolved once the patient was started on azithromycin for Campylobacter gastroenteritis.…”
Section: Discussionmentioning
confidence: 64%
“…Based on Rio Grande Valley demographics with high prevalence of murine typhus in the area, the patient was treated empirically with doxycycline until her agglutinins were negative [ 18 ]. In this clinical case, the neurological and gastrointestinal symptoms rapidly resolved once the patient was started on azithromycin for Campylobacter gastroenteritis.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for the geographic concentration of cases in these areas remain unclear as the vector and reservoir hosts are relatively ubiquitous. Murine typhus is not a nationally notifiable disease in the United States and one likely factor may be underdiagnoses/misdiagnoses in non-endemic regions [ 101 ]. A study conducted in Mexico City, Mexico, demonstrated a 15% (207 of 1382 individuals tested) seroprevalence of R. typhi in healthy adult blood donors, suggesting contact with R. typhi vectors and reservoir hosts may be relatively common in portions of North America [ 102 ].…”
Section: Flea-borne Rickettsiae (In Alphabetical Order)mentioning
confidence: 99%
“…However, sometimes murine typhus may cause severe complications if the diagnosis and treatment are not timely [7]. In recent years, many regions have reported murine typhus cases with severe complications, such as pneumonia, pancreatitis, and septic shock [8][9][10]. There are only a few regions still monitor murine typhus, such as Texas, Hawaii, California and Taiwan [7,11].…”
Section: Introductionmentioning
confidence: 99%